Optimasi Keuntungan Penjualan Stempel Menggunakan Program Linier Metode Grafik Berbasis QM for Windows - Muhammad T Hidayah; Heru Sutejo; Ryandika R Saputra; Thomas O Ansanay; Fauzia R Lessy; Nataniel T A Mamu (CV Edujavare Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in determining the optimal production quantity due to their limited resources. One such problem is experienced by Cendrawasih Art Printing, which produces stamps and signboards under constraints related to raw materials and production time. This study aims to optimize production profits by applying the Linear Programming method using a graphical approach supported by QM for Windows software. The research data were obtained through direct observation and interviews with the business owner to collect information regarding profit per unit of product, raw material requirements, and available working time capacity. The decision variables in this study consist of the production quantities of stamps (X₁) and signboards (X₂), with the objective function aimed at maximizing profit subject to various available resource constraints. The results indicate that the optimal production combination is 20 units of stamps and 5 units of signboards per week, yielding a maximum profit of IDR 950,000. The calculations using the graphical method and their verification through QM for Windows produced consistent solutions, thereby confirming the accuracy of the model employed. Sensitivity analysis further reveals that the availability of stamp handles and production time are the primary constraints affecting optimal profit. Therefore, the Linear Programming method using a graphical approach can serve as an effective decision-support tool for MSME owners in determining efficient production strategies and maximizing business profits.